The levels of protection in Slovene agriculture and policy implications - Rednak M.; Erjavec E.; Turk J. (Agricultural price reform under transition in Bulgaria, Romania, and Slovenia, 1998)
The objective of this paper is to measure the level of agricultural protection in Slovenia using conventional methodology. The Producer Subsidy Equivalent (PSE) and the Nominal Agricultural Assistance Coefficient for producer (NAPC) were used to determine protection levels during the initial stages of economic transition (1992-95). The results show positive protection with a level in 1995 about the some as the OECD average and a little lower than EU protection levels. Commodity-wise the highest levels of protection are for sugar beet, milk and beef, while coarse grains and poultry meat hold relatively low support levels. The paper acknowledges that a current tendency towards increasing price protection in Slovenia should be curtailed and gradually replaced by on effective budget support policy.